UJI AKTIVITAS ANTIBAKTERI DARI EKSTRAK KASAR KULIT BATANG MANGROVE Avicennia marina (FORKS.) VIERH TERHADAP PERTUMBUHAN BAKTERI Escherichia coli - Marta Ina Kii; Andriani Rafael; Sonya T.M Nge (Indigenous Biologi : Jurnal Pendidikan dan Sains Biologi, 2020)
ABSTRACTMangrove plant is one of the coastal ecosystems that dominates the coastal area and has the potential to be developed in the prevention of various diseases both infections in aquaculture and as a natural treatment medium for humans, because the secondary metabolite compound contained can be efficacious as an anti-bacterial. The purpose of this study was to determine the effect of A. marina mangrove bark extract against the growth of E. coli and the optimum concentration of A. marina mangrove bark extract in inhibiting the growth of E. coli bacteria. The method used in this study is a laboratory experimental method with 4 treatments namely a concentration of 55 mg/mL, 60 mg/mL, 65 mg/mL, 70 mg/mL and 1 control without administration of extract with 3 replications. Observation result of inhibition zone diameters were statistically analyzed using a one-way analysis was performed using the SPSS program version 16.0. the results showed that the rough extract of A. marina mangrove bark affected the growth of E. coli bacteria. This can be seen from the concentrations used starting from 55 mg/mL, 60 mg/mL, 65 mg/mL and 70 mg/mL having average inhibition zones ranging from 26 mm, 27.33 mm, 27.66 mm and 28.66 mm. thus the higher the concentration of the extract used, the greatervthe inhibition formed. Keywords : Avicennia marina, Escherichia coli, Antibacterial